2018
DOI: 10.1109/tnsre.2018.2851617
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Vibro-Tactile Feedback Prevents Object Slippage in Hand Prostheses More Intuitively Than Other Modalities

Abstract: In the case of a hand amputation, the affected can use myoelectric prostheses to substitute the missing limb and regain motor functionality. Unfortunately, these prostheses do not restore sensory feedback, thus users are forced to rely on vision to avoid object slippage. This is cognitively taxing, as it requires continuous attention to the task. Thus, providing functionally effective sensory feedback is pivotal to reduce the occurrence of slip events and reduce the users' cognitive burden. However, only a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…Marasco et al (2018) showed that inducing the kinesthetic illusion in TMR amputees improved real-time feedback (as well as other properties, highlighted below). Cipriani's group used discreteevent feedback (expanded below), and found an improvement in performance (Clemente et al, 2016;Aboseria et al, 2018). All these studies share a common theme of tapping into a use for feedback that is not redundant with the role played by vision.…”
Section: Continuous Feedback For Real-time Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Marasco et al (2018) showed that inducing the kinesthetic illusion in TMR amputees improved real-time feedback (as well as other properties, highlighted below). Cipriani's group used discreteevent feedback (expanded below), and found an improvement in performance (Clemente et al, 2016;Aboseria et al, 2018). All these studies share a common theme of tapping into a use for feedback that is not redundant with the role played by vision.…”
Section: Continuous Feedback For Real-time Controlmentioning
confidence: 99%
“…They showed that humans incorporate this feedback, even in the presence of vision, during a grasp and lift task (Cipriani et al, 2014). More recently they have shown that the discrete feedback improves performance (Clemente et al, 2016) and reduces slips (Aboseria et al, 2018). Discrete feedback was largely off the map of prosthetic feedback until the work of Johansen and Cipriani.…”
Section: Discrete Feedback For Event Confirmationmentioning
confidence: 99%
“…However, these studies were conducted while controlling a virtual setup [35][36][37] and/or while blocking the incidental (visual and auditory) feedback sources [18,31,36,38]. Some recent studies showed benefits of feedback in realistic, clinical settings [32,[39][40][41][42][43]. However, other experiments in realistic settings failed to show functional improvements in performance [13,19,20,44,45] or demonstrated some benefits of feedback only in specific conditions [13,14,40].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the opinion of tactile feedback on improving prosthesis performance is still a matter of controversy. Most studies concluded that the integration of tactile feedback improved the performance of prosthesis manipulation [16][17] [18], although there were some studies showing an improvement only with certain conditions or users, or even little difference when compared with the non-feedback condition [19]. In some cases, clinical therapists claimed that amputees with only visual and audio feedback could acquire comparable prosthetic grasping performance with the performance of a closed-loop condition if the rehabilitation/training process was adequate enough.…”
Section: Introductionmentioning
confidence: 99%